Penggunaan Tindak Tutur Pada Mantra Dalam Ritual â€œDidin Kotaâ€ Pada Suku Lidak, Kabupaten Belu, Provinsi Nusa Tenggara Timur - -, Adi Iswani (Educreative : Jurnal Pendidikan Kreativitas Anak, 2021)
This study entitled the Use of Speech Actions in incantations in the "Didin Kota" Ritual of the Matabesi Makerek Badaen (Lidak) Tribe, Belu Regency, Nusa Tenggara Timur Province. This re-search is based on the reality that incantations are still used by the people of Nusa Tenggara Timur, especially Belu Regency in the Didin Kota ritual. Research to describe and explain the use of speech acts in incantations in the ritual "Didin Kota" in the Matabesi Makerek Badaen (Lidak) Tribe. This research is a qualitative descriptive study. The subject of this research is the city didin ritual. The techniques used in this study were interviews, recordings, and documenta-tion. So that the results of interviews with informants can be transcribed. The data of this re-search is the use of speech acts in the incantations in the ritual "Didin Kota" in the Matabesi Makerek Badaen (Lidak) tribe, Belu Regency, Nusa Tenggara Timur. The results showed the use of illocutionary speech acts in the form of directive speech acts. Based on the use of speech acts in incantations in the ritual "Didin Kota" from the transcripts of interviews with informants, it is hoped that the public can deepen and understand more about the use of speech acts in incanta-tions in general and in detail. So you can find out the intent and purpose of the incantations spoken.